Rapeseed oil with anti-wear additives on the four ball tester. Issue 1 (December 2020) - Ionescu, T F; Guglea, D; Dima, D; Georgescu, C; Deleanu, L
Abstract: This paper presents a tribological characterization on the four ball tester, for three lubricants: rapeseed oil and this vegetal oil with two anti-wear nano additives (TiO2 and ZnO, respectively). The lubricants were obtained at laboratory scale by a particular regime of sonication. Each additive was added in: 0.25%, 0.50% and 1% mass concentrations. The tests were done for the following loads and sliding speeds: 100…300 N and 0.38…0.69 m/s. The authors selected three tribological parameters for evaluating the tribological behavior of lubricants formulated based on rapeseed oil and two nano additives (ZnO and TiO2 ): average of friction coefficient during 1 h test, wear scar diameter (WSD) and the temperature of lubricant bath at the end of the test.